Fixed Drug Eruption of the Penis Secondary to Sulfamethoxazole-Trimethoprim. (2006) - Lawrentschuk, Nathan; Pan, David; Troy, Andrew
Abstract : Penile lesions are encountered in a variety of fields from family medicine practice through urology, to sexual health specialists. It is important that practitioners consider and recognize fixed drug eruptions of the penis while being able to initiate appropriate treatment in order to avoid misdiagnosis and avoidable stress. In summary, withdrawal of the offending medication and initiation of corticosteroid therapy remain the cornerstones of treatment of fixed drug eruptions of the penis.